Feminism : the march toward equal rights for women - Dearman, Jill (Inquire & investigate., 2019)
Explores the history of feminism, covering its "waves" from the first wave's focus on winning the right to vote up to the present and feminism's focus on intersectionality and the importance of the "#MeToo" movement. Includes profiles of key feminist figures in history, news articles touching upon feminism, and a glossary.